Lost on the frontline, and lost in the data: COVID-19 deaths among Filipinx healthcare workers in the United States - Escobedo, Loraine A.; Morey, Brittany N.; Sabado-Liwag, Melanie D.; Ponce, Ninez A. (Frontiers in Public Health, 2022)
Background Filipinx Americans working in healthcare are at risk for COVID-19 death but lack consistent mortality data on healthcare worker deaths. The lack of disaggregated data for Asian subgroups proliferates anti-Asian structural racism as the needs of high-risk groups are systematically undetected to merit a proper public health response. We work around this aggregated data problem by examining how the overrepresentation of Filipinxs in healthcare contributes to COVID-19 mortality among Asian American populations. Methods To overcome the lack of COVID-19 mortality data among Filipinx American healthcare workers, we merged data from several sources: Kanlungan website (the only known public-facing source of systematically reported mortality data on Filipinx healthcare workers nationally and globally), National Center for Health Statistics, and 2014–2018 American Community Survey. We examined county-level associations using t-tests, scatterplots, and linear regression. Findings A higher percentage of Filipinxs among Asian Americans was correlated with a higher percentage of COVID-19 decedents who are Asian Americans (r = 0.24, p = 0.01). The percentage of Filipinx in healthcare remained a strong predictor of COVID-19 deaths among Asian Americans even after adjusting for age, poverty, and population density (coef = 1.0, p < 0.001). For every 1% increase in Filipinx among the healthcare workforce, the percentage of Asian American COVID-19 decedents increased by 1%. Interpretation Our study shows that the overrepresentation of Filipinxs in healthcare contributes to COVID-19 mortality disparities among Asian Americans. Our findings advocate for systems change by practicing anti-racist data agendas that collect and report on Asian subgroups for effective real-time targeted approaches against health inequities.